Blood Hypothermic Storage and Erythrocyte Cryopreservation in Dogs - Zhegunov, Gennadiy; Denysova, Olga; Zhegunova, Galina (Problems of Cryobiology and Cryomedicine, 2023)
This review presents the analysis of reported data on the current methods for blood hypothermic storage and erythrocyte cryopreservation in dogs. The relevance of designing and improving the techniques for canine erythrocyte cryopreservation, cryobanking, as well as the application of cryopreserved blood components for transfusion were substantiated. The features of canine blood hypothermic storage and specific use of cryoprotectants with various modes of their action were considered. The advantages of applying DMSO and combined cryopreservatives during low temperature storage of canine erythrocytes were specified. Probl Cryobiol Cryomed 2022; 32(4):245–255